Medical Laboratories Quality Management and Challenges in Ethiopia: A Systematic Review - Mesganaw B; Fenta A; Hibstu Z; Belew H; Misganaw K; Belayneh M (Dove Medical Press, 2023)
Bewket Mesganaw,1 Abebe Fenta,1 Zigale Hibstu,1 Habtamu Belew,1 Ketema Misganaw,2 Mekuriaw Belayneh1 1Department of Medical Laboratory Science, Debre Markos University, Debre Markos, Ethiopia; 2Department of Public Health Emergency, Ethiopian Public Health Institute, Addis Ababa, EthiopiaCorrespondence: Bewket Mesganaw, Email bewketm@gmail.comBackground: Although based on a single system, each laboratory should have their own quality management system, in Ethiopia, quality management systems in medical laboratories were introduced in 2009 with the aim of improving the quality of services.Objective: This review was designed to evaluate the status of quality management practice and challenges among medical laboratories in Ethiopia.Methods: A systematic qualitative review of the literature was made by searching the international electronic bibliographic database of PubMed (NML), web of science (TS), google scholar, African journals online (AJOL) and Cochrane Library.Results: Thirty-six full-text articles, which were published between 2010 and 2022, were included in this review. In this review, 33 of 36 (91.7%) studies showed that status of quality management practice in Ethiopian medical laboratories was limited. As a result, the quality of medical laboratories was inadequate. The main challenges were problems associated with laboratory professionals (35/36=97.2%), inadequate support from management bodies (21/36=58.3%), limited on-job training access (8 /36=22.2%) and high workload (5/36=13.8%).Conclusion: The status of quality management practice among medical laboratories in Ethiopia is limited. The main quality compromising factors were problems associated with laboratory professionals, inadequate support from management bodies, high workload, and limited on-job training access. Therefore, all responsible stakeholders should focus on ensuring Quality Management Systems and the system should be applied in all Medical laboratories. Only this will ensure the improvement of quality within medical laboratories across Ethiopia.Keywords: quality, medical laboratory, quality management system, implementation, challenges